2022
DOI: 10.3389/fphar.2022.1030406
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pharmacists’ interventions within the Closed Loop Medication Management process on medication safety: An analysis in a German university hospital

Abstract: Background: Single elements of the Closed Loop Medication Management process (CLMM), including electronic prescribing, involvement of clinical pharmacists (CPs), patient individual logistics and digital administration/documentation, have shown to improve medication safety and patient health outcomes. The impact of the complete CLMM on patient safety, as reflected in pharmacists’ interventions (PIs), is largely unknown.Aim: To evaluate the extent and characterization of routine PIs performed by hospital-wide CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The consequences of this lack of knowledge among physicians have been widely reported. A recent study found that over 65% of identified drug-related problems were linked to drug indications (37.3%) and dosing (29.6%) without specifying particular medications ( Berger et al, 2022 ). In this study, physicians had a high acceptance rate (93%) for interventions suggested by pharmacists, indicating that they trust the pharmacists' knowledge as drug experts ( Berger et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of this lack of knowledge among physicians have been widely reported. A recent study found that over 65% of identified drug-related problems were linked to drug indications (37.3%) and dosing (29.6%) without specifying particular medications ( Berger et al, 2022 ). In this study, physicians had a high acceptance rate (93%) for interventions suggested by pharmacists, indicating that they trust the pharmacists' knowledge as drug experts ( Berger et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a CLMM is characterised by computerised physician order entry (CPOE), prescription validation by clinical pharmacists (CP), as well as patient-orientated logistics, and electronic documentation of administration. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Such a CLMM is characterised by computerised physician order entry (CPOE), prescription validation by clinical pharmacists (CP), as well as patient-orientated logistics, and electronic documentation of administration. 5 Based on the CPOE, patient-orientated logistics can be processed by the UDDS in a hospital pharmacy, which also provides the basis for medication reconciliation by the CPs. For medication reconciliation, duplicate prescriptions, over/under dosing, as well as interactions and contraindications must be taken into account.…”
Section: Introductionmentioning
confidence: 99%